The Unique and Evidence-Based Meningococcal Vaccine for Hajj and Umrah Pilgrims - Abdul Muttalif, Abdul Razak Bin (International Journal of Human and Health Sciences (IJHHS), 2025)
This lecture will delve into the significance of the unique, evidence-based meningococcal vaccine for pilgrims undertaking the Hajj and Umrah journeys. Meningococcal disease, caused by Neisseria meningitidis, poses a serious risk in the densely populated environments of these religious gatherings. The speaker will explore the epidemiology of meningococcal disease, particularly in the context of mass gatherings, and discuss the specific strains prevalent in the region. The session will highlight the development and approval of the meningococcal vaccine tailored for pilgrims, including its formulation, efficacy, and safety profile. Speaker will also review current vaccination guidelines mandated by international and local health authorities, and the importance of vaccination for all travellers to protect against outbreaks. Additionally, we will present recent evidence from studies demonstrating the vaccine’s effectiveness in preventing infections among pilgrims. By the end of this lecture, participants will gain a comprehensive understanding of the importance of the meningococcal vaccine, enabling them to advocate for its use and ensure the safety and well-being of pilgrims during their spiritual journeys. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S10